Three-dimensional braiding of continuous regenerated cellulose fibres. (March 2016) - Huber, Tim; Kuckhoff, Britta; Gries, Thomas; Veit, Dieter; Pang, Shusheng; Graupner, Nina; Müssig, Jörg; Staiger, Mark P
A growing interest in biocomposites leads to the extension of commonly used three-dimensional braiding processes for composite preforming to cellulose-based fibres. A rayon fibre (Cordenka™) is processed on an Institut für Textiltechnik 3D rotary braiding machine, generally used for the processing of stronger and stiffer glass and carbon fibres. A rectangular profile was produced from 32 yarns and the braiding angle of the yarn was analysed. Analysis of the fibre tensile properties during the different processing steps revealed only a minor reduction in fibre strain. The fibre strength and Young's modulus were unaffected by the braiding process showing that 3D rotary braiding can be extended to biobased fibres without any required changes.